Youth screen-time behaviour is associated with cardiovascular risk in young adulthood: the European Youth Heart Study. (January 2014) - Grøntved, Anders; Ried-Larsen, Mathias; Møller, Niels Christian; Kristensen, Peter Lund; Wedderkopp, Niels; Froberg, Karsten; Hu, Frank B; Ekelund, Ulf; Andersen, Lars B
Aims: We prospectively examined the association of TV viewing, computer use, and total screen time in adolescence, and change in these behaviours, with cardiovascular disease (CVD) risk factors in young adulthood. Methods and results: This was a prospective cohort study among Danish men and women ( n  = 435) followed for up to 12 years. Adiposity, blood pressure (BP), triglycerides, high-density lipoprotein (HDL), glucose, insulin, and self-reported TV viewing and computer use were obtained in adolescence and in young adulthood. A continuous metabolic syndrome z-score was calculated as the sum of standardized values of each risk factor (inverse of HDL). In multivariable-adjusted analyses, TV viewing and total screen time in adolescence were positively associated with adiposity, triglycerides, and metabolic syndrome z-score in young adulthood ( p  < 0.05). Individuals who increased their TV viewing, computer use, or total screen time with more than 2 hours/day from adolescence to young adulthood had 0.90 (95% CI 0.12 to 1.69), 0.95 (95% CI 0.01 to 1.88), and 1.40 (95% CI 0.28 to 2.51) kg/m 2 higher body mass index, respectively, in young adulthood compared with individuals who remained stable or decreased their viewing time. Insulin and metabolic syndrome z-scores were also higher among individuals who increased their TV viewing, computer use, or total screen time more than 2 hours/day compared with individuals who remained stable or decreased their viewing time ( p  < 0.05). Conclusions: Prolonged TV viewing and total screen time during leisure time in adolescence, and increases in these behaviours, are associated with unfavourable levels of several cardiovascular risk factors in young adulthood.